Cost-effectiveness of gallbladder histopathology after cholecystectomy for benign disease. Issue 6 (2nd November 2020) - Lundgren, L; Henriksson, M; Andersson, B; Sandström, P
Abstract: Background: The prevalence of incidental gallbladder cancer is low when performing cholecystectomy for benign disease. The performance of routine or selective histological examination of the gallbladder is still a subject for discussion. The aim of this study was to assess the cost-effectiveness of these different approaches. Methods: Four management strategies were evaluated using decision-analytical modelling: no histology, current selective histology as practised in Sweden, macroscopic selective histology, and routine histology. Healthcare costs and life-years were estimated for a lifetime perspective and combined into incremental cost-effectiveness ratios (ICERs) to assess the additional cost of achieving an additional life-year for each management strategy. Results: In the analysis of the four strategies, current selective histology was ruled out due to a higher ICER compared with macroscopic selective histology, which showed better health outcomes (extended dominance). Comparison of routine histology with macroscopic selective histology resulted in a gain of 12 life-years and an incremental healthcare cost of approximately €1 000 000 in a cohort of 10 000 patients, yielding an estimated ICER of €76 508. When comparing a macroscopic selective strategy with no histological assessment, 50 life-years would be saved and the ICER was estimated to be €20 708 in a cohort of 10 000 patients undergoing cholecystectomy. Conclusion: A macroscopic selective strategy appears to be the most cost-effective approach. Graphical Abstract: The objective of this study was to assess the cost-effectiveness of routine and selective gallbladder histopathology when performing cholecystectomy for benign disease. The most important factor for cost-effectiveness was found to be the cost and number of histological analyses, due to large numbers of cholecystectomies relative to low prevalence of incidental gallbladder cancer. The model indicated that the macroscopic selective strategy was the most beneficial. longer placements improve outcomes